A novel pathway for sorting to intralumenal vesicles of multivesicular endosomes involved in organelle morphogenesis - Theos, Alexander C. (2006)
Cargo partitioning into intralumenal vesicles (ILVs) of multivesicular endosomes underlies such cellular processes as growth factor down-regulation, viral budding, and biogenesis of lysosome-related organelles including melanosomes. Here we show that the melanosomal protein, Pmel17, is sorted into ILVs by a novel mechanism that is conserved in non-pigment cells and is dependent upon lumenal determinants. ILV targeting of Pmel17 is unaffected by mutagenesis of cytoplasmic lysine and cysteine residues or replacement of the cytoplasmic domain, indicating independence of ubiquitylation, and unlike ILV targeting of ubiquitylated cargo, is insensitive to functional inhibition of Hrs and ESCRT complexes. Chimeric protein and deletion analyses indicate that two N-terminal lumenal sub-domains are necessary and sufficient for ILV targeting. Pmel17 fibril formation, which occurs during melanosome maturation in melanocytes, requires a third lumenal sub-domain and proteolytic processing that itself requires ILV localization. These results establish a novel Hrs- and perhaps ESCRT-independent pathway of ILV sorting by lumenal determinants and a requirement for ILV sorting in fibril formation.